THE CHARACTERISTICS OF THE COGNITIVELY GIFTED LEARNERS: GUIDELINES FOR MALAYSIAN TEACHERS IN TEACHING LANGUAGE - Mohd Sham Kamis; Muhammad Nazir Alias; Noriah Mohd Ishak; Md Jais Ismail, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Teaching gifted learners sometimes can be frustrated due to the endless questions from them and because of their asynchronous development that indicates physical and emotional development as well as cognitive abilities in learning. In fostering this common situation, teachers or lecturers have, perhaps, the greatest opportunity in cultivating the language knowledge for gifted learners in the classroom. This article discusses the action of teachers that focuses on identifying characteristics of gifted learners in reading Arabic text. Besides, gifted learners have special needs that require interventions, such as academic acceleration and academic enrichment. Additionally, without appropriate modifications of strategy in teaching, gifted learners are at risk of underachievement in their academic life. Apart from that, the authors of this article intend to mention a few theories related to this situation in learning the language. The findings indicate that all interviewees were asked to discuss their feelings and the excitement of learning Arabic sentences. Eventually, these findings can be used to inform gifted secondary school educational practices and specifically, how to design interventions that optimize learning experiences for secondary school of gifted learners in comprehending Arabic sentences.